Analysis of interfacial effects in all-solid-state batteries with thiophosphate solid electrolytes - Neumann, A; Randau, S; Becker-Steinberger, K; Danner, T; Hein, S; Ning, Z; Marrow, J; Richter, FH; Janek, J; Latz, A (American Chemical Society, 2020)
All-solid-state batteries (ASSBs) present a promising route toward safe and high-power battery systems in order to meet the future demands in the consumer and automotive market. Composite cathodes are one way to boost the energy density of ASSBs compared to thin-film configurations. In this manuscript, we investigate composites consisting of β-Li3PS4 (β-LPS) solid electrolyte and high-energy Li(Ni0.6Mn0.2Co0.2)O2 (NMC622). The fabricated cells show a good cycle life with a satisfactory capacity retention. Still, the cathode utilization is below the values reported in the literature for systems with liquid electrolytes. The common understanding is that interface processes between the active material and solid electrolyte are responsible for the reduced performance. In order to throw some light on this topic, we perform 3D microstructure-resolved simulations on virtual samples obtained via X-ray tomography. Through this approach, we are able to correlate the composite microstructure with electrode performance and impedance. We identify the low electronic conductivity in the fully lithiated NMC622 as material inherent restriction preventing high cathode utilization. Moreover, we find that geometrical properties and morphological changes of the microstructure interact with the internal and external interfaces, significantly affecting the capacity retention at higher currents.